ความรู้ ภาพลักษณ์ การรับสื่อ และความต้องการบทบาทกิจการ เพื่อสังคมของประชาชนในกรุงเทพมหานคร - วาณิชานุรักษ์ชัย, พรชนก; มีนะกรรณ, นาวิน (RMUTSB ACADEMIC JOURNAL, 2014)
บทคัดย่อไม่สมบูรณ์ Knowledge, image, perception and need of social enterprise roles of people in Bangkok The research aimed to study influence of knowledge, image, and perception about social enterprise on the need of Bangkok citizens for social enterprise roles in the economic, social and environmental aspects as well as its overall picture. Samples were 400 residents of Bangkok. Data was collected through questionnaires, and multiple regression analysis was used to test the hypothesis with the level of significant difference at 0.05. It was found that the knowledge, the image, and the perception about social enterprise affect the need for roles in social enterprise in all aspects. This study could be beneficial to make social enterprise aware that the development of social enterprise for people is to increase their need for social enterprise roles, and social enterprise should encourage those people by educating them, establishing the good image and updating them on social enterprise.